Survei Kondisi Fisik Siswa Ekstrakurikuler Futsal Putra di SMA Negeri Se-Kota Batu - Syafikri, Mohamad Iqbal; Amiq, Fahrial (Universitas Maritim AMNI Semarang, 2024)
The aim of this research was to determine and assess the level of physical condition of male futsal extracurricular students at State High Schools in Batu City. This type of research uses a quantitative descriptive survey design, the variable studied is the level of physical condition. In this study, the sample taken from the entire population who took part in the men's futsal extracurricular at State High Schools in Batu City amounted to 90 students using a total sampling technique. The results of the physical condition of male futsal extracurricular students at SMAN Se-Kota Batu include the